Impact of prophylactic use of antimicrobials in abdominal surgery in two tertiary level hospitals - Shusmita Saha; Syed Ashrafuzzaman (Bangladesh Pharmacological Society, 2008)
Post-surgical infections are polymicrobial and it is an important cause of morbidity and mortality. The combination of ciprofloxacin plus metronidazole as well as several ß-lactum based regimens are commonly used regimens for the treatment of patients with such infections.  Three hundred patients (age range 25-40 years) were taken from two teaching hospitals for interventional study. When patients were selected for appenditectomy or cholecystectomy, either ciprofloxacin plus metronidazole or cephalosporin plus metronidazole were given intravenously. The patients were then divided into 4 groups. Group I and Group II received drugs ciprofloxacin plus metronidazole and cephalosporin plus metronidazole in SSMC respectively and Group III and Group IV received drugs ciprofloxain plus metronidazole and cephalosporin plus metronidazole in DNMC respectively. There were 33 cases of infections out of total 300 study subjects. It was observed that in SSMC among ciprofloxacin plus metronidazole; the rate of infection was 10.6% and cephalosporin plus metronidazole group was 14.6% while that in DNMC the rate were 8% and 10.6% respectively. The overall rate of infection was 11%.